A study of the outcomes of conservative treatment of meniscal injuries in the knee - نظام, عدي; أحمد جوني , (Latakia University Journal -Medical Sciences Series, 2022)
Objective: The aim of this study is to evaluate the effectiveness of conservative treatment of meniscal injuries in the knee, identify its indications and determine the most effective conservative program in managing these injuries. Patients and methods A prospective study conducted for the period of one year (June 2021 – June 2022) at Tishreen University Hospital in Latakia, Syria involving 61 patients that were divided into two groups: one group underwent a conservative program based on intra-articular platelet-rich plasma (PRP) injections and the other underwent a conservative program based on oral dietary supplements (Glucosamine). Lysholm knee score was recorded before the treatment and then 6 months after, and by comparing the two results, we adopted the difference as a criteria for clinical improvement. Results: We found a statistically significant difference between the two treatment groups in terms of the average degree of improvement on the Lysholm knee score. The best results were recorded in the group that was treated using intra-articular PRP injection, with similar improvement rates between males and females, the right and left knee. We observed that the average percentage of improvement was higher in the younger patients, athletes, second degree tears, peripheral zone injuries (the red zone), longitudinal tears and especially recent injuries, while observing the negative impact of osteoarthritic changes in the knee in addition to radial and horizontal tears on improvement. Conclusion: Conservative treatment of meniscal injuries provides an appropriate solution in many cases if one takes into account: age of the patient, time of occurrence of the injury, location of the injury, degree of the tear and the degree of osteoarthritic changes in the knee. We found that platelet-rich plasma (PRP) injections in the knee is superior to the treatment based on oral supplements, especially in cases of: younger patients, in athletes, in the absence of osteoarthritic changes, in second degree tears, in longitudinal tears and in injuries that are under 12 weeks old. The results of conservative treatment of meniscal injuries are not encouraging in older patients, in cases that are accompanied by osteoarthritic changes in the knee or in injuries that are over 12 weeks old Keywords: Meniscal injuries, conservative treatment, platelet-rich plasma, lysholm.